Microbial assessment of Dental Unit Waterline System (DUWS)/ Chua Chong Sing - Chua, Chong Sing (2012)
Introduction: Dental Unit Waterline System (DUWS) is an interconnected water network found inside a dental chair unit (DCU) that allows water to pass through and deliver to the patient’s mouth during treatment. Many previous studies demonstrated the DUWS water was often heavily contaminated and might pose a risk of infection to the patients as well as dental personnel. Objective: To determine the sanitary level of output water from DCUs and assess the effectiveness of silver-coated tubing used in DCU in reducing microbial counts in DUWS water. Methods: Water from sources which include the air-water syringe, low speed handpiece, high speed handpiece and distilled water (control) were sampled from 13 DCUs. The temperature and pH of each sample were measured and the microbial counts of the total aerobic bacteria, total coliform, faecal coliform, Escherichia coli, faecal streptococci and Pseudomonas aeruginosa were determined using conventional microbiological procedures. Based on PCR products, the 16S rDNA gene sequence of bacteria isolated from the water samples were determined and used for identification. An in vitro model simulating the tubing of a DCU was setup in the laboratory using silver-coated and conventional polyurethane tubes. A microbial suspension comprising of similar bacteria earlier identified in the DUWS outgoing water was passed through the tubing in cycles of stagnation and flushing to mimic the routine operation of a DUWS. The effectiveness of the tubing in preventing biofilm formation was compared and assessed by the counts of adhering bacteria and observed under scanning electron microscope. Results: The average pH of the outgoing water was slightly acidic at pH 5.4-5.5 at an average temperature of 23°C. The outgoing water was found free of pathogenic contaminant but highly loaded with four types of bacteria identified as Sphingomonas rhizogenes (17.9%), Sphingomonas dokdonesis (79.5%), Sphingomonas mucosissima (1.1%) and Methylobacterium radiotolerans (1.5%). The interior surface of both polyurethane and silver-coated tubes showed extensive biofilm formation and the outgoing water was heavy with bacterial counts. No significant difference in biofilm formation and bacterial contamination in the outgoing water were found in both types of tubing (P>0.05). Conclusion: The microbial load in the outgoing water from DUWS in the clinic under study was high and failed to meet the recommendation by American Dental Association. Silver-coated tubing was not effective in preventing biofilm formation nor reducing microbial load in DUWS water when compared with polyurethane tubings.